Effects of propafenone on electrophysiologic changes caused by alteration of left ventricular afterload in anesthetized rabbits - Qiu Han-Ying; Li Di-Jun; Mao Huan-Yuan (Acta Pharmacologica Sinica; Vol 18, No 6 (November 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study effects of propafenone (Pro) on ventricular electrophysiologic changes caused by alteration of left ventricular afterload of rabbit heart. METHODS: Before and after i.v. Pro 3 mg.kg-1, changing afterload of left ventricle (LV), occurrence of ventricular arrhythmia, left ventricular diastolic thresholds (VDT), relative refractory period (RRP), effective refractory period (ERP), dispersion of refractory period, and ventricular fibrillation threshold (VFT) were recorded. RESULTS: Increasing afterload of LV increased temporal dispersion of RRP and ERP [from 11 +/- 4 and 6 +/- 3 ms to 18 +/- 8 and 13 +/- 8 ms (+delta P = 8.4 +/- 2.9 kPa) individually (P < 0.05)] and decreased VFT [from 5.5 +/- 1.0 V to 3.9 +/- 0.9 V (P < 0.01)]; Ventricular arrhythmia was seen in all rabbits. But reducing left ventricular afterload did not alter the electrophysiologic parameters in LV and did not induce ventricular arrhythmia. Pro i.v. prolonged RRP and ERP, increased VDT and VFT (P < 0.01); Increasing or decreasing left ventricular afterload did not cause much alteration of ventricular electrophysiologic parameters (P > 0.05). CONCLUSION: Pro inhibited increase of dispersion of refractory period and decrease of VFT caused by increase of left ventricular afterload and has an effect of anti-ventricular arrhythmia.